Oltre la stratificazione costitutiva: per una lettura dialettico-ricorsiva del rapporto tra passività e attività in Husserl - Nobili, Filippo (Philosophy Kitchen - Rivista di filosofia contemporanea, 2020)
The paper revises Husserl’s analytic effort to articulate a stratigraphic model of intentional constitution, i.e. made of different layers of passive and active performances. Indeed, genetic phenomenology allows to sketch an alternative model of a dialectic-recursive type, more suitable to deal with the concreteness of experience.